International classification... - Campos, Astério (Revista de Biblioteconomia de Brasília, 1975)
São analisados os seguintes documentos: INTERNATIONAL CLASSIFICATION. Journal on theory and pratice of universal and special classification systems and thesauri. München: Verlag Dokumentation, 1974— v. 1. Semestral. WOJCIECHOWSKI, Jerry A., ed. Conceptual basis of the classification of knowledge. Proceedings of the Ottawa Conference on the Conceptual Basis of the Classification of Knowledge, October 1st to 5th, 1971. München: Verlag Dokumentation, 1974. 503 p. THIRD INTERNATIONAL STUDY CONFERENCE ON CLASSIFICATION RESEARCH, Bombay, 6-11 January, 1975. Trabalhos apresentados. VICKERY, B. C. Classification and indexing in science. 3.ed. London: Butterworths, 1975. 228 p. ISBN 0 408 70662 7. MALTBY, Arthur. Sayer’s manual of classification for librarians. 5.ed. London: André Deutsch, 1975. 336 p. ISBN 0 233 96603 X.